Climate Responsive Economic Recovery : Post-Pandemic Opportunities in Mashreq - Ahmad, Ali; Ranade, Monali (World Bank, Washington, DC, 2021)
In Mashreq, climate change and fragility form a vicious cycle wherein current fragility hinders climate action and climate threats will exacerbate fragility. The Coronavirus (COVID-19) pandemic has brought an acute disruption to the global economy, yet its most profound effects have been felt in weak and fragile states, including Mashreq countries. Reimagining a post-Covid-19 climate-responsive economic recovery presents a critical opportunity to break away from this cycle and align economic, development, and climate agendas. This report highlights some of the opportunities available for Mashreq countries, focusing on Iraq, Jordan and Lebanon, to couple climate action with post-pandemic economic recovery. The main audience of this report are the governments, policy makers, development community and stakeholders in Mashreq interested in exploring climate responsive opportunities to support economic recovery.